Цифрова дипломатія: впровадження електронних візових послуг в Україні - Яковюк, І. В.; Цвелих, М. П. (НДІ ПЗІР НАПрН України, 2022)
Дослідження присвячене висвітленню актуальних проблем впровадження в Україні електронних візових послуг в рамках більш широкої проблеми – цифрової дипломатії. У статті співвідносяться поняття «e-diplomacy», «Intertet diplomacy» та «socialmedia diplomacy». Розкриваючи взаємозв’язок між загальним поняттям електронної дипломатії та питанням візових послуг, автори доходять висновку, що для реалізації цих послуг мережа Інтернет виступає як спеціальна платформа для подання, розгляду, а в окремих випадках і надання готового документу, що надає право на в’їзд до країни. Це може бути спеціальний урядовий веб-сайт, який призначений для обробки заявок іноземців на отримання візи або спеціальний веб-застосунок для міграційних питань. Акцентовано увагу на тому, що використання концепції електронної візи успішно апробоване в зарубіжних країнах. Переважно нею користуються держави із суворою імміграційною політикою. Для того щоб полегшити та систематизувати роботу їхніх дипломатичних, консульських та міграційних установ, було створено система електронної авторизації. Підкреслено, що у країнах Шенгенської зони відбувається формування власної системи електронної авторизації Europeran Travel Information and Autorisation System (ETIAS). Хоча ETIAS безпосередньо не є проїзним візовим документом, але його заповнення буде обов’язковим для громадян країн з безвізовим режимом, які будуть відвідувати країни Шенгенської зони. Дана новація спрямована на оптимізацію міграційного контролю. Впровадження інституту електронної візи як елемента цифрової дипломатії надає можливість швидкого двостороннього контакту та зв’язку, а отже сприяє виконанню поставлених у Стратегії державної міграційної політики України на період до 2025 року цілей. Problem setting. In the XXI century almost all aspects of human life are covered by the processes of scientific and technological progress. The sphere of law has not been spared from these processes: thanks to information technologies, certain legal services have become more accessible and convenient. In Ukraine, this was manifested not only in the creation of electronic versions of national legislation and various electronic registers, but also in the provision of administrative services through the relevant services. Consular activities involve the provision of services. Amendments to the procedure for the provision of such administrative services and the provision of such services in electronic form can accelerate the process of digitalization of Ukraine, as well as unload the work of diplomatic institutions and reduce corruption risks. Analysis of recent researches and publications. In the national legal literature in recent years, much attention has been paid to e-government (Kravets R., Kuzhda T., Romaniv T.), while almost no attention is paid to the analysis of the state of implementation of electronic services (Solomko Y.), in particular electronic visa services (Kolomiets G., Makhoniuk O., Mulska O.), which determines the relevance and practical significance of this study. Target of research is to investigate the introduction of electronic services for foreign citizens to obtain a visa to enter or transit through the territory of Ukraine, as well as forecasting the prospects of using electronic visas in Ukraine based on the analysis of foreign experience of using this type of visa. Article’s main body. For the implementation of visa services, the Internet acts as a special platform for submitting, processing and, in some cases, providing a ready-made document granting the right to enter the country. This may be a special government website designed to process visa applications of foreigners or a special web application for migration issues. The use of the e-visa concept has been successfully tested in foreign countries and in the EU. It is mainly used by the states with strict immigration policies in order to facilitate and systematize the work of their diplomatic, consular and migration institutions, an electronic authorization system was created. Conclusions and prospects for the development. As a result of the study of the phenomenon of e-diplomacy, analysis of the practice of using electronic services for the provision of administrative services by diplomatic and consular institutions, analysis of the legislation of the countries with advanced e-visas, the state of implementation of e-visas in Ukraine was assessed and the prospects for their development were determined. The steps of the state in this direction are part of a large reform of digitalization of the country, the implementation of which will improve the image of Ukraine in the world, make our country attractive for tourists, as well as optimize the visa issuance procedure, relieving the workload of diplomatic and consular missions, authorized persons for processing visa applications and the Migration Service of Ukraine. The introduction of the e-visa institute as an element of digital diplomacy provides an opportunity for quick bilateral contact and communication, and thus contributes to the achievement of the goals set in the Strategy of State Migration Policy of Ukraine until 2025.
Keywords: цифрова дипломатія; консульське право; консульська установа; електронні візові послуги; Україна; digital diplomacy; consular law; consular office; electronic visa services; Ukraine